An Inductor-Less, Discontinuous Current Source Gate Driver for SiC Devices - Pilli N.K.; Chauhan A.K.; Singh S.K.; Xiong X. (My University, 2025)
EMI has remained a limiting factor in driving the SiC MOSFETs to its maximum potential and achieving a trade-off between EMI and switching losses is a major challenge for the designers. In this paper, an inductor-less, discontinuous current source gate driver (DCSD) is proposed. Exclusion of inductor results in a compact footprint and easy integration in IC form. The absence of predriver for proposed DCSD reduces the complexity of the driver, making it easier to control and implement. In addition, very low propagation delay is attained with the proposed DCSD which allows SiC MOSFETs to switch at higher switching frequencies with low losses. The proposed DCSD is compared with a commercially available reference gate driver for SiC MOSFET, and the results are analyzed and validated with hardware prototype. A better trade-off between switching losses and EMI is obtained with the proposed driver, where during turn-off, a 65% reduction in dVds/dt and 45% reduction in dId/dt is achieved at the cost of 33% increase in the total switching loss. © 2013 IEEE.